The Impact of COVID-19 on Adolescent Mental Health: Preliminary Findings From a Longitudinal Sample of Healthy and At-Risk Adolescents - Cohen, Zsofia P.; Cosgrove, Kelly T.; DeVille, Danielle C.; Akeman, Elisabeth; Singh, Manpreet K.; White, Evan; Stewart, Jennifer L.; Aupperle, Robin L.; Paulus, Martin P.; Kirlic, Namik (Frontiers in Pediatrics, 2021)
Background The COVID-19 pandemic has brought on far-reaching consequences for adolescents. Adolescents with early life stress (ELS) may be at particular risk. We sought to examine how COVID-19 impacted psychological functioning in a sample of healthy and ELS-exposed adolescents during the pandemic. Methods A total of 24 adolescents (15 healthy, 9 ELS) completed self-report measures prior to and during the COVID-19 pandemic. The effect of COVID-19 on symptoms of depression and anxiety were explored using linear mixed effects analyses. Results With the onset of the pandemic, healthy but not ELS-exposed adolescents evidenced increased symptoms of depression and anxiety (ps<.05). Coping by talking with friends and prioritizing sleep had a protective effect against anxiety for healthy adolescents (t=-3.76, p=.002). Conclusions On average, this study demonstrated large increases in depression and anxiety in adolescents who were healthy prior to the COVID-19 pandemic, while ELS-exposed adolescents evidenced high but stable symptoms over time.